(untitled) (Semiárida, 2025)
The objective of this study was to evaluate the effect of nitrogen and phosphorus fertilization on the production and quality of Panicum coloratum L. (perennial millet), in a soil in southeastern La Pampa. The experiment was conducted on a perennial millet pasture in the town of Jacinto Arauz. The fertilization treatments were 0, 40 and 80 kg N ha-1 with and without P (fixed dose of 10 kg P ha-1) called: T- P- N40, N40+P- N80 and N80+P. The experimental design was randomized blocks with three replications. The accumulated dry matter (MSAC kg ha-1) (sum of three cuts during the growth cycle), the growth rate (TC, kg MS ha-1 day-1), the water use efficiency (EUA, kg MS ha-1 mm-1) and the apparent use of nitrogen (EUN) were quantified. In addition, deferred dry matter (DMS) and quality parameters were quantified: crude protein (PB) and dry matter digestibility (DMS). The response to fertilization in the MSAC showed increases with values of 51 % in the P treatment and 59 % with N80+P compared to the MSTD, indicating a greater response in biomass production in the MSAC compared to the MSTD. Nitrogen fertilization produced positive responses in forage production. The dose of 80 kg N ha-1 was the most effective during its growth cycle (MSAC). For deferred forage, the combination of 40 kg N ha-1 + P proved to be the best strategy. Nitrogen fertilization improved forage quality, with higher % of PB in treatments that only received N. The combination with N and P is a viable strategy to increase the production and quality of perennial millet in the Southeast of La Pampa.